f + 15

- 2/3f

11 answers

To simplify the expression \( f + 15 - \frac{2}{3}f \), we first need to combine the like terms involving \( f \).

  1. Rewrite \( f \) as \( \frac{3}{3}f \) to have a common denominator: \[ f = \frac{3}{3}f \]

  2. Now substitute this into the expression: \[ \frac{3}{3}f - \frac{2}{3}f + 15 \]

  3. Combine the \( f \) terms: \[ \left(\frac{3}{3} - \frac{2}{3}\right)f + 15 = \frac{1}{3}f + 15 \]

So, the simplified form of the expression is: \[ \frac{1}{3}f + 15 \]

5
-15

To simplify the expression \(5 - 15\):

\[ 5 - 15 = -10 \]

So, \(5 - 15\) equals \(-10\).

a + 12
-3/4a

To simplify the expression \( a + 12 - \frac{3}{4}a \), we first combine the like terms involving \( a \).

  1. Rewrite \( a \) as \( \frac{4}{4}a \) to have a common denominator: \[ a = \frac{4}{4}a \]

  2. Now substitute this into the expression: \[ \frac{4}{4}a - \frac{3}{4}a + 12 \]

  3. Combine the \( a \) terms: \[ \left( \frac{4}{4} - \frac{3}{4} \right) a + 12 = \frac{1}{4}a + 12 \]

So, the simplified form of the expression is: \[ \frac{1}{4}a + 12 \]

8
-12

To simplify the expression \(8 - 12\):

\[ 8 - 12 = -4 \]

So, \(8 - 12\) equals \(-4\).

4 • (-4)
And
4 • (1/4a)

Let's simplify each expression one at a time.

  1. For \(4 \cdot (-4)\): \[ 4 \cdot (-4) = -16 \]

  2. For \(4 \cdot \left(\frac{1}{4}a\right)\): \[ 4 \cdot \left(\frac{1}{4}a\right) = \frac{4}{4}a = 1a = a \]

So, the results are:

  • \(4 \cdot (-4) = -16\)
  • \(4 \cdot \left(\frac{1}{4}a\right) = a\)
8h - 16 = -4h - 10
What does h equal?

To solve the equation \(8h - 16 = -4h - 10\) for \(h\), follow these steps:

  1. Add \(4h\) to both sides to get all \(h\) terms on one side: \[ 8h + 4h - 16 = -10 \] This simplifies to: \[ 12h - 16 = -10 \]

  2. Add 16 to both sides to isolate the \(h\) term: \[ 12h - 16 + 16 = -10 + 16 \] This simplifies to: \[ 12h = 6 \]

  3. Divide both sides by 12 to solve for \(h\): \[ h = \frac{6}{12} = \frac{1}{2} \]

So, the solution is: \[ h = \frac{1}{2} \]